Full-scale laboratory tests of geosynthetic reinforced unpaved roads on a soft subgrade. Issue 4 (23rd August 2021) - Khoueiry, N.; Briançon, L.; Riot, M.; Daouadji, A.
Abstract : In this study, a large-scale laboratory test was developed to analyze the contribution of geogrid reinforcement to the improvement of unpaved roads. A detailed experimental protocol was established regarding the road base soil preparation, installation, and soil compaction procedure. Eight tests were performed under a circular plate load test in a box 1800 mm in width, 1900 mm in length, and 1100 mm in height. Under this configuration, three repeat tests were performed to verify the developed protocol. Furthermore, the plate load tests were used to compare different road base thicknesses and geogrid types. Once the developed protocol was confirmed, three tests, using the developed simulator accelerator of traffic (SAT), were performed. Indeed, the same road base configuration was tested, but this time it was placed in a box 5000 mm in length. The prepared road base was subjected to two different loadings: a specific plate load and a traffic load. The results showed the efficiency of the geogrids, the influence of the road base thickness, and the role of the loading type. Moreover, it demonstrated different mobilized mechanisms of the geogrid, depending on the type of product.